PERAN PENDAMPING TERHADAP PEMBERDAYAAN KELOMPOK TANI KAKAO DI KABUPATEN BOLAANG MONGONDOW UTARA - Juwita Janeke Eman; Jenny ., Baroleh; Agnes E. Loho (Sam Ratulangi University, 2017)
This study aims to determine the role of facilitators who facilitate farmer groups, especially in cocoa crops and know the various obstacles faced by the accompaniment in the assistance activities of cocoa farmer groups in North Bolaang Mongondow Regency. The study lasted for three months from February to April 2017. The data collected in the form of primary and secondary data. Primary data collected through interviews with 5 farmer groups and taken by deliberate were 3 farmers group of Advanced and 2 groups of Beginner Farmer Group. Each group of farmers is taken as many as 6 people consisting of the management of farmer groups namely chairman, secretary, treasurer and 3 members. Total of respondents amounted 30. Secondary data were obtained from the Office of Agriculture and District Offices in North Bolaang Mongondow. Data analysis was used descriptive analysis. The results of this research showed that the counselor was instrumental in empowering the cocoa farmer groups in both the beginner and advanced farmer groups in intensification and rehabilitation activities. The role of companion is categorized as a very important role that is 88.3%. This can be seen from the corective and enhacement in the way of gardening. The constraints faced by counselors, especially at the beginner level farmers, are the fear of to take risk of failure in production so that they have not dared to try new technologies.